Anti-rotavirus antibody measurement in a rotavirus vaccine trial: Choice of vaccine antigen in immunoassays does matter. Issue 1 (31st December 2023) - Wang, Xiaoqian; Velasquez Portocarrero, Daniel E.; Cortese, Margaret M.; Parashar, Umesh; Zaman, Khalequ; Jiang, Baoming
ABSTRACT: In a clinical trial of Bangladeshi infants who received three doses of RotaTeq (ages 6, 10, and 14 weeks), we did a head-to-head assessment of two vaccine virus strains to measure rotavirus IgA in sera. Serum samples collected at pre-dose 1 (age 6 weeks) and post-dose 3 (age 22 weeks) were tested for rotavirus IgA by EIA by using the matching vaccine strain (RotaTeq) and a different vaccine strain (Rotarix) as antigens. Overall, rotavirus IgA seropositivity and titers with each antigen were compared. At age 22 weeks (N = 531), the proportion of infants who tested rotavirus IgA seropositive was similar when measured using the RotaTeq (412/531 [78%]) or the Rotarix antigen (403/531 [76%]) in the EIA. However, the IgA geometric mean titer was higher when measured using the RotaTeq antigen as compared to that measured using the Rotarix antigen [218 (95%CI: 176–270) vs. 93 (77–111), p < .0001]. We have compared two globally licensed vaccines, the human monovalent, and the pentavalent reassortant, as antigens on a RotaTeq cohort, resulting in higher estimations of IgA antibodies in the same sample when measured using the RotaTeq antigen. Our findings support matching vaccine antigens in EIA for the most desired immunogenicity testing of the RotaTeq vaccine.